A Systematic Review of Supported Accommodation Programs for People Released From Custody. (June 2018) - Growns, Bethany; Kinner, Stuart A.; Conroy, Elizabeth; Baldry, Eileen; Larney, Sarah
One of the challenges that people recently released from custody face is securing housing. Many individuals rely on supported accommodation programs for housing in the immediate post-release period. However, the value of supported accommodation programs in producing positive criminal justice and health outcomes for people released from custody has not been widely examined. This article reviews the current literature on supported accommodation programs and the elements of these services that contribute to positive outcomes for individuals released from custody. We focused on programs that provided temporary, transitional group residences for adults recently released from a correctional setting. The systematic review identified only nine publications that met the inclusion criteria. Studies were frequently at high risk of bias and few consistent findings emerged about either effectiveness of accommodation programs or program characteristics associated with participant outcomes. Methodologically rigorous research is needed to determine the effectiveness of post-release supported accommodation programs.